Landing patterns in netball: analysis of an international game. Issue 2 (June 1992) - Hopper, D; Lo, S K; Kirkham, C; Elliott, B
Abstract : The passing and landing patterns among netball players were investigated by examining all the 595 passes in an international match between Australia and New Zealand. Intra-class correlations were used to test inter-observer reliability. The independence of two variables was tested using a Pearson chi 2 test and a contingency coefficient was used to assess the degree of association between variables. An inter-rater reliability in the identification of movement patterns was 0.99. Most of the landings observed in this match were on the forefoot and not the hindfoot as generally reported in controlled experiments. Only 14% of the players leapt to receive a pass compared with 76% reported earlier under controlled environments. The distribution of passing techniques unexpectedly showed that approximately 50% of all the players did not reach for the ball as it was thrown directly to them. However, over 70% of the players threw straight passes which were mainly received in the chest quadrant and other types of passes such as loop, bounce and rebound were used less frequently. Nearly 50% of all players used a right-handed pass to dispose of the ball, while the next most popular pass was to use both hands (40.2%). Landing and passing patterns differed between players in different positions. Footfall patterns on landing after a catch were associated with the trajectory of the ball.